2022
DOI: 10.3390/healthcare10010084
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship between Fetal Alcohol Spectrum Disorder (FASD) and Criminal Justice: A Systematic Review

Abstract: Prenatal alcohol exposure is considered one of the main causes of preventable birth disorders; however, it represents the main form of developmental delay in the world. Among the so-called secondary disabilities related to fetal alcohol spectrum disorder (FASD), there is a close connection with criminal behavior. This systematic review aims to provide up-to-date information about the relationship between FASD subjects and criminal justice analyzing different aspects. In light of the results of this review, a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…There have also been ongoing calls for legislative and policy reform in Canada to address the challenges presented by FASD in criminal courts, including two bills that aimed to codify FASD as a mitigating factor and increase the availability of court-ordered FASD assessments but were not passed into law (e.g., Bill C-583, Bill C-235), as well as syntheses including a national consensus conference (Binnie & Trussler, 2013). Therefore, Canadian examples and case law may prove helpful in informing legislation, policy, and practice shifts in other jurisdictions (Gibbs & Sherwood, 2017; Sessa et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…There have also been ongoing calls for legislative and policy reform in Canada to address the challenges presented by FASD in criminal courts, including two bills that aimed to codify FASD as a mitigating factor and increase the availability of court-ordered FASD assessments but were not passed into law (e.g., Bill C-583, Bill C-235), as well as syntheses including a national consensus conference (Binnie & Trussler, 2013). Therefore, Canadian examples and case law may prove helpful in informing legislation, policy, and practice shifts in other jurisdictions (Gibbs & Sherwood, 2017; Sessa et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…FAS, FASD, Foetal Alcohol Spectrum Disorder, Foetal alcohol syndrome, justice, PAE, prenatal alcohol exposure, paediatric neuropsychological assessment, youth detention living skills. Similarly, Sessa et al (2022) reported justice-involved individuals with PAE were more likely to experience difficulties with impulse control, executive functioning, academic achievement, adaptive behaviours and social skills.…”
Section: Introductionmentioning
confidence: 92%
“…Neurodevelopmental difficulties can include impairment in executive functioning, attention and information processing, language, and motor problems (Mattson et al, 2019). These difficulties contribute to a range of adverse outcomes that may be considered secondary to the neurodevelopmental challenges, including poor educational attainment, social and behavioral problems (Easey et al, 2019; Jacobson et al, 2021; Sessa et al, 2022; Tsang et al, 2016), and physical health issues (Caputo et al, 2016) across childhood, adolescence, and adulthood (Wilhoit et al, 2017), highlighting the importance of robust and rigorous assessment processes that allow for early identification and tailored intervention.…”
Section: Introductionmentioning
confidence: 99%